ANALISIS PERAMALAN MENGGUNAKAN ARIMA PADA INDEKS HARGA PERDAGANGAN BESAR INDONESIA KELOMPOK KOMODITI PERTANIAN TAHUN 2000-2019 - Bimo Setyawan; Nur Indah Riwajanti; Sidik Ismanu (STIE Mahardhika, 2020)
Purpose of this research was to forecasting analysis using arima in indonesia's big trade price index group of agricultural commodities in 2000-2019. In this study aims to see the forecast prediction on the Agricultural Commodity Big Price Index in the next 1 years. In Indonesian economy, indicators for looking at economic development in general and as an ingredient in market and monetary analysis are by measuring the average intertemporal price changes of a package of goods in wholesale trade. In Indonesia in the period of 2000 until 2019, agricultural commodities in the index The Big Trade Price is the most dominant commodity among other commodities. This study uses method the Arima model with several stages of identifying, estimating, diagnosing and forecasting. the results of this study have shown that the arima model can forecast in the agricultural sector.